2021
DOI: 10.1111/jcmm.16805
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of BUB1 suppresses tumorigenesis of osteosarcoma via blocking of PI3K/Akt and ERK pathways

Abstract: Osteosarcoma (OS) is a primary malignant bone tumour that mainly affects teenagers, with patients displaying poor prognosis. Budding uninhibited by benzimidazoles 1 (BUB1), a type of serine/threonine kinase that is linked to pro‐tumorigenic phenomena, has not been well studied in OS. Hence, this study aimed to explore the role of BUB1 in OS. The expression of BUB1 in OS specimens and cell lines was assessed using immunohistochemistry and Western blot analysis. Univariate and multivariate analyses were applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…OS is manifested with elevated metastasis rate and poor prognosis and is hardly treated because of limited treatment strategies [ 1 , 2 ]. Consequently, it is vital to further realize the molecular mechanism of OS occurrence and development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OS is manifested with elevated metastasis rate and poor prognosis and is hardly treated because of limited treatment strategies [ 1 , 2 ]. Consequently, it is vital to further realize the molecular mechanism of OS occurrence and development.…”
Section: Discussionmentioning
confidence: 99%
“…Osteosarcoma (OS) is the most prevalent primary invasive bone tumor, frequently existing in young men and children under 20 years of age. Like other tumors, OS has a high degree of malignancy, many OS patients are prone to recurrence or metastasis, and the prognosis is poor [ 1 ]. Although surgical techniques and chemotherapy have improved in recent years, the survival rate of many patients has not improved much, and the 5-year survival rate is still less than 70% [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on PPI network, genes with top 5 highest degree were identified, including cdk1 , cdc20 , bub1 , plk1 , and aurkb. In human clinical studies, cdk1 , cdc20 , bub1 , and plk1 were commonly associated with bone diseases, including rheumatoid arthritis, osteoarthritis, and bone-related tumors. Therefore, these results indicated that aberrant expression of the selected hub genes might be responsible for caudal malformation in this study. Our results highlighted the negative effects of TDCIPP on the skeletal system of fish.…”
Section: Resultsmentioning
confidence: 56%
“…In addition, transforming growth factor- β (TGF- β ) signal transduction, which regulates cell proliferation and differentiation, may be regulated by BUB1 [ 44 ]. In osteosarcoma, inhibition of BUB1 markedly suppressed cell proliferation, cell migration, and invasion through blocking of the PI3K/Akt and ERK signaling pathways [ 45 ]. Our results confirmed that BUB1 plays a vital role in the regulation of MYC, Wnt, Notch, and Hedgehog pathways, which are sharply associated with stemness signaling [ 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%